Konsep dan Pengaplikasian Pembelajaran Kooperatif Tipe Jigsaw Tingkat MI/SD - Muhammad Rayhan Saputra; Lu`luil Maknun (Jurnal IAI Bunga Bangsa Cirebon, 2022)
The purpose of writing this article is to find out the basic concepts, implementation steps, characteristics of the advantages and disadvantages as well as the effectiveness of the application of jigsaw cooperative learning in teaching and learning activities in MI or SD level classes. The writing method is carried out using a literature study or literature research method, using research materials in the form of journals, articles and physical and digital books sourced from Google Scholer, national library applications, and other media, which are then explored and adapted to the topic raised as the theme of the material. discussion. Learning in the implementation process is known by the teacher as the owner of the main role who explains all learning materials and students only accept so that the interaction becomes passive. Problems sometimes arise when teachers determine the learning model that will be used to deliver predetermined subject matter to students. The jigsaw cooperative learning model is a model that is implemented by focusing on students with group work in the form of small groups. Studying in groups will provide a new atmosphere in learning so as to minimize student boredom and improve student learning outcomes Abstrak Tujuan penulisan artikel ini untuk mengetahui konsep dasar, langkah-langkah penerapan, ciri khas kekurangan dan kelebihan serta efektivitas penerapan pembelajaran kooperatif tipe jigsaw dalam kegiatan belajar mengajar di kelas tingkat MI atau SD. Metode penulisan dilakukan dengan metode studi pustaka atau literature review, menggunakan bahan penelitian berupa jurnal, artikel dan buku fisik maupun digital yang bersumber dari google scholer, aplikasi perpustakaan nasional, dan media lainnya, yang kemudian di dalami dan disesuaikan dengan topik yang diangkat sebagai tema materi pembahasan. . Pembelajaran dalam proses pelaksanaannya dikenal guru sebagai pemilik peran utama yang menjelaskan seluruh materi pembelajaran dan peserta didik hanya menerima sehingga interaksi menjadi pasif. Permasalahan terkadang muncul pada guru saat menentukan model pembelajaran yang akan digunakan untuk menyampaikan materi pelajaran yang telah ditentukan kepada peserta didik. Model pembelajaran kooperatif jigsaw merupakan model yang dilaksanakan dengan memusatkan pada siswa dengan kerja kelompok dalam bentuk kelompok kecil. Belajar secara berkelompok akan memberikan suasana baru dalam pembelajaran sehingga meminimalisir kebosanan peserta didik dan meningkatkan hasil belajaran siswa